Comparative study of host-associated and commercial probiotic effects on serum and mucosal immune parameters, intestinal microbiota, digestive enzymes activity and growth performance of roach (Rutilus rutilus caspicus) fingerlings - Reza Tarkhani (2020)
© 2019 Elsevier Ltd The study aimed to isolate host-associated probiotic (HAP) lactic acid bacteria from intestine of adult Caspian roach and compare the efficacy of HAP with a commercially available probiotic strain (Pediococcus acidilactici) on the growth and feed utilisation, digestive enzymes and systemic and mucosal immune system of roach fingerling. The HAP strain isolated from roach intestine was Enterococcus faecium strain CGMCC1.2136. The experiment was a simple completely randomized design and lasted for eight weeks. Two hundred and seventy fish with an average weight of 12 g randomly distributed into nine tanks. The trial consisted of three treatments with three respective replications. During the experimental period, fish received basal diet without any bacterial supplementation (as the control group), basal diet enriched with 108 CFU g−1 HAP or 107 CFU g−1 CP. At the end of the experiment, serum immune parameters of those fish fed HAP including alkaline phosphatase activity, total protein content, total immunoglobulin level, lysozyme activity and complement activity (ACH50) were significantly higher that other experimental groups (P < 0.05). Similarly, dietary supplementation of HAP resulted in better mucosal immune parameters in comparison to control group and commercial probiotic administration (P < 0.05). Intestinal heterotrophic bacteria and autochthonous LAB counts of those fish fed HAP were significantly higher than other experimental groups at the end of the experiment as well as 15 days seizing probiotic administrations (P < 0.05). Fish fed with HAP containing diet presented significantly higher amylase, lipase and protease activity in comparison to the CP fed fish and the control group (P < 0.05). Growth indices of those fish fed HAP were significantly higher than other treatments (P < 0.05). The highest carcass protein and ash content along with the lowest body moisture content belonged to those fish received HAP (P < 0.05). In conclusion, the use host-HAP resulted in better immune competence and growth performance and it seems aquaculture sector should probably focus on the development of probiotics isolated from the cultured species instead of using terrestrial probiotics with greatly different requirements and environmental conditions.